Effectiveness of GeoGebra on Botswana TVET students’ performance on linear equations - Sekgoma, Amantle Mico (Asian Journal of Contemporary Education, 2024)
The purpose of this study was to investigate the comparative effects of using GeoGebra software and traditional teaching approaches on the performance of TVET students in linear equations. The study followed a quasi-experimental design with a non-equivalent group consisting of pre- and post-test measures. The population of the study consisted of TVET learners from 14 Brigades in the southern region of Botswana. Using the convenience sampling technique, two TVET institutions (n=41) participated in the study. One institution formed the experimental group, whereas the other formed the control group. The study did not employ random participant selection, as the control group and the experimental group comprised pre-existing, intact classes from the participating institutions. GeoGebra software was used in the experimental group, while the control group was taught using the traditional approach with no technology incorporation. Similar pre- and post-tests were administered to both groups to measure the comparative effects of each teaching method on the performance of learners. A constructivist theory framed the study. A t-test was used to analyze the data with α = 0.05, and the findings showed a significant difference in the mean scores between the control group and the experimental group (t = 2.188, p = 0.008 < α) in the post-test. These results indicated that students in the experimental group outperformed those in the control group. Overall, the results of this study showed that GeoGebra enhanced student performance in linear equations as compared to traditional methods of teaching.